Diversity of Forest and Shrub Communities as a Result of Site History and of Extensive and Intensive Forest Management (Glinno Ługi Case Study) - Woziwoda, Beata; Ambrożkiewicz, Katarzyna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
The paper presents the diversity of natural and anthropogenic forest communities occurring in post-cultivated fields in Glinno Ługi. An impoverished fresh pine forest association (Leucobryo-Pinetum) and nine secondary forest communities have been distinguished in the transect line (1.16 km in length). Factors influencing the structure and species composition of recent forest communities, such as habitat properties, previous land use forms and the intensity of forest management, are described.